2012
DOI: 10.1002/eji.201141800
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of MUC1 expression and its recognition by CD8+ T cells on the surface of malignant pleural mesothelioma cells treated with HDACi

Abstract: Research into new treatments against malignant pleural mesothelioma (MPM) is of great interest, as this aggressive cancer is often resistant to conventional therapies. One potential strategy is the use of epigenetic drugs, such as 5-aza-2 0 -deoxycytidine (5-azaCdR), a DNAhypomethylating drug, and valproate (VPA), a histone deacetylase inhibitor (HDACi). Indeed, these drugs not only trigger MPM cell death, but also induce the expression of cancer testis antigens recognized by CD8 1 T cells, such as New York-es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Among the four classes of HDACs, VPA preferentially inhibits class I HDACs (HDAC1, 2, 3, and 8). 27 Although VPA has been reported to directly inhibit tumor cell proliferation and attenuate tumor immunogenicity via HDAC inhibition, 28,29 the immune regulation ability of VPA in the TME has rarely been addressed. In this study, we clearly showed that VPA could effectively relieve the immunosuppressive TME through a reduction in tumor-infiltrating M-MDSCs, leading to a reduction of tumor burden ( Figure 6(e)).…”
Section: Discussionmentioning
confidence: 99%
“…Among the four classes of HDACs, VPA preferentially inhibits class I HDACs (HDAC1, 2, 3, and 8). 27 Although VPA has been reported to directly inhibit tumor cell proliferation and attenuate tumor immunogenicity via HDAC inhibition, 28,29 the immune regulation ability of VPA in the TME has rarely been addressed. In this study, we clearly showed that VPA could effectively relieve the immunosuppressive TME through a reduction in tumor-infiltrating M-MDSCs, leading to a reduction of tumor burden ( Figure 6(e)).…”
Section: Discussionmentioning
confidence: 99%
“…For example, zebularine, via the upregulation of IDO, has also been shown to decrease immunogenicity, but only at high doses; at low doses, the immunogenicity is increased [102]. The balance between activated and repressing immunological response appears to be both cell and agent specific, as HDAC inhibition has been shown to both increase expression of tumour associated antigens, for example gp100 in murine melanoma cells [103], and in other systems to downregulate tumour antigens, for example Muc1 in mesothelioma cells [104]. This highlights the complex nature of epigenetic modulation, and the likelihood that it will not work as expected in all cancers or all individuals.…”
Section: Epigenetics Of Cancermentioning
confidence: 99%
“…Histone deacetylase (HDAC), on the other hand, removes acetyl groups and suppresses the gene transcription process. HDAC inhibitors have been shown to restore expression of TAA and cancer-testis antigens such as NY-ESO-1 (6163), enhance MHC class I and II expression(64, 65), and upregulate PD-L1 expression(66, 67). In preclinical models, Kim et al reported tumor eradication in 80% of mice bearing either CT26 colon cancer or 4T1 breast cancer, treated with combination of epigenetic-modulators (5-AZA plus entinostat, a HDAC inhibitor) and checkpoint inhibitors (anti-CTLA4 plus anti-PD1), but not checkpoint inhibitors alone, accomplished by depletion of myeloid derived suppressive cells (MDSC) (68).…”
Section: The Potential Mechanisms Of Combined Benefits Of Targetedmentioning
confidence: 99%